EMD: Empirical Mode Decomposition and Hilbert-Huang spectral analyses in Python - Quinn, AJ; Lopes Dos Santos, V; Dupret, D; De Ozorio Nobre, A; Woolrich, M (Open Journals, 2021)
The Empirical Mode Decomposition (EMD) package contains Python (>=3.5) functions for analysis of non-linear and non-stationary oscillatory time series. EMD implements a family of sifting algorithms, instantaneous frequency transformations, power spectrum construction and single-cycle feature analysis. These implementations are supported by online documentation containing a range of practical tutorials.